Diversity of Endophytic Fungi in The Root, Leaf, Stolon and Petiole of Asiatic Pennywort (Centella asiatica) - Dwi Ningsih Susilowati; Amelia Rakhmaniar; Nani Radiastuti; Ika Roostika (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
Endophytic fungi live in healthy tissues of many plants, including in medicinal plant such as Asiatic pennywort (Centella asiatica). These fungi exist in different parts of the plant as symbionts. The study aimed to isolate endophytic fungi from various parts of Asiatic pennywort of Malaysia accession and characterize their nature. Three individual plants of Asiatic pennywort (3 months-old) were obtained from the Sringanis Medicinal Garden in Bogor. The endophytes were isolated on Malt Extract Agar. The community structures of the endophytes were analyzed based on their diversity, colonization, dominance index, and relative frequency of occurrence of the isolated endophytic fungi. A total of 78 isolates have been obtained from three individual plants and clustered into 22 morphotypes consisted of 18 morphotypes of Ascomycota and 4 morphotypes of Basidiomycota divisions. The stolons harbored more endophytes (22.9 %) followed by leaf (16.7 %), root (11.8 %), and petiole (7.6 %). The diversity index was classified as medium category with the highest result (1.91) was found in the root, followed by leaf (1.79), stolon (1.75), and petiole (1.29). The most dominant endophytes were identified as Ceratobasidium sp., Colletotrichum sp, and Fusarium sp. Ceratobasidium sp. has the highest dominance index (0.02). UPGMA cluster analysis grouped the endophytic fungi into distinct clusters based on the plant parts origin. This study implied that stolon was the the most suitable part of Asiatic pennywort for isolating endophytic fungi. Further study is required to examine the role of the endophytic fungi to produce secondary metabolites in Asiatic pennywort.